DESCRIPTION OF WOMEN'S STRESS WITH PROGRAM IN VITRO FERTILIZATION – EMBRYO TRANSFER - sherly jeniawaty (Health Notions, 2022)
Introduction : In Vitro Fertilization is one solution to the problem of infertility. In Vitro Fertilization is the process of fertilization of egg cells and sperm cells outside the woman's body (in a liquid medium in a glass cup). In Vitro Fertilization (IVF) has several types, one of which is Embryo Transfer. IVF-ET treatment itself lasts a long time, which is approximately 50 months. So that women who undergo IVF-ET often experience increased stress, the cause is either from themselves, lack of support from partners, family, and the surrounding social environment. The purpose of this Literature Review is to analyze several research results regarding the description of women's stress with the in vitro fertilization– Embryo program. Method : The type of research used is Literature Review using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) and JBI checklist. The search results through 4 databases (Google Scholar, NCBI, PubMed, and Elsevier) found 1,055 journals, then selected so that the remaining 13 journals matched the inclusion criteria. Journal search adjusted for the last five years. Results : The results of a review of 13 journals found that 1 journal showed stress for IVF-ET women in the form of worry, 8 journals described stress for women with IVF-ET in the form of anxiety, 1 journal described stress for IVF-ET women in the form of intrapersonal sensitivity, 2 journals showed stress for IVF women. -ET in the form of isolating themselves from the social environment, 1 journal shows that IVF-ET women's stress can be in the form of sleep pattern disturbances, 1 journal discusses IVF-ET women's stress in the form of alexithymia, and 1 journal discusses IVF-ET women's stress in the form of decreased sexual arousal. Discussion : Based on a review of 13 journals that have been analyzed, the most dominant picture of stress in women with IVF-ET programs is the occurrence of anxiety. And of course, further research is needed to analyze other stress features experienced by women with IVF-ET programs. Keywords: Stress, Women, In Vitro Fertilization